2019
DOI: 10.3233/jad-180797
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hyaluronan and TSG-6 in Association with Neuropathologic Changes of Alzheimer’s Disease

Abstract: Little is known about the extracellular matrix (ECM) during progression of AD pathology. Brain ECM is abundant in hyaluronan (HA), a non-sulfated glycosaminoglycan synthesized by HA synthases (HAS) 1–3 in a high molecular weight (MW) form that is degraded into lower MW fragments. We hypothesized that pathologic severity of AD is associated with increases in HA and HA-associated ECM molecules. To test this hypothesis, we assessed HA accumulation and size; HA synthases (HAS) 1–3; and the HA-stabilizing hyaladher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…5b) and HA ( Fig. 5c) levels were both significantly higher in modsevere CAA brains (n = 8 for western blot and n = 26 for HA ELISA) vs no CAA brains (n = 4 for western blot and n = 14 for HA ELISA), which was similar to what we have previously found in high ADNC vs not ADNC [31].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…5b) and HA ( Fig. 5c) levels were both significantly higher in modsevere CAA brains (n = 8 for western blot and n = 26 for HA ELISA) vs no CAA brains (n = 4 for western blot and n = 14 for HA ELISA), which was similar to what we have previously found in high ADNC vs not ADNC [31].…”
Section: Resultssupporting
confidence: 88%
“…In this context, TSG-6 likely organizes HA molecules into a crosslinked network and plays a protective role in response to brain injury/inflammation [27,29,30]. Our previous studies have found greater amounts of HA and TSG-6 in brains with high ADNC relative to those with no ADNC [31].…”
Section: Introductionmentioning
confidence: 91%
“…In particular, HA removal was sufficient to drive a hyperexcitable state, which is characteristic of neurodevelopmental disorders, including epilepsy, intellectual disability, and autism spectrum disorders 12,35,40 . Conversely, our observation that HA decreases excitatory synapse formation could have implications for aging and Alzheimer's Disease, both of which exhibit HA accumulation and synapse loss [69][70][71][72] . In particular, aging is associated with loss of synapses that form on highly plastic thin spines 69 , which resemble the filopodia-like spine precursors involved in prenatal synaptogenesis 30,48,73 .…”
Section: Discussionmentioning
confidence: 80%
“…TSG6 mRNA and protein were also significantly increased in AD brains. 80 It is generally accepted that CSPG accumulation is increased during neurodegeneration. 59 Similar to what has been reported during CNS scar formation, the characteristic lesions of Abeta and neurofibrillary tangles NFT are surrounded by reactive gliosis as measured by GFAP positive astrocytes.…”
Section: Glycocalyx and Associated Ecm Changes In Agingmentioning
confidence: 99%